(3CSQGQ GdJQhjL aj YUQ GdYhdeIs (3JLGQH TQcGJ OhdjI aj GdJQhjLs - (3YHO GdUHhQ(B, (3eMSf aJMis ((3GdbGgQIs (3eLehYI Gdfjd GdYQHjIs, 2001)
(3CSGSjGJ GdJQhjL;GdeYGQV GdJLGQjI,eWHhYGJ GdJQhjL,RjGQI GdCShGb GdNGQLjI,GdOYGjI hGdEYdGf,GdJQhjL YHQ THcI GdCfJQfJ,JfTjW GdeHjYGJ,GdJQhjL GdeHGTQ,Jbhje HQGeL GdJQhjL,JLGQH TQcGJ OhdjI,CSQGQ fLGM GdjHGfjjf aj GdJQhjL,GdJQhjL aj GdbQf GdhGMO hGdYTQjfs
Keywords: (3GdJShjbs